(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this article is to highlight the massive structure of Sri Athinatha Perumal temple at Alwarthirunagari in Eral taluk of Thoothukudi district. Alwarthirunagari is located 26 km east from Tirunelveli. Constructed in the Dravidian style of architecture, the temple is glorified in the Naalayira Divya Prabandham, the early medieval Tamil canon of the Alvar saints from the 6th–9th centuries CE. It is one of the 108 Divya Desams dedicated to Vishnu, who is worshipped as Adinathar and his consort Lakshmi as Athinathanayagi. The temple is also classified as a Navatirupathi, the nine temples revered by Nammalvar located in the banks of Tamiraparani river. The temple is the most prominent among the nine Navatirupathi temples.